American Indians' Family Health Concern on a Northern Plains Reservation: "Diabetes Runs Rampant Here". Issue 1 (3rd September 2015) - Martin, Donna; Yurkovich, Eleanor; Anderson, Kara
Abstract: Objectives: The objective was to identify significant family health concerns from the perspective of adult tribal members residing in a reservation setting on the Northern Plains of the United States. Findings were used to cocreate culturally appropriate strategies to address the most significant family health concern. Design and Sample: A focused ethnography within a participatory framework was employed. An advisory council, comprised of seven tribal members, guided the research team. A purposive sampling technique with a snowball process was used. Twenty‐one adult tribal members volunteered to participate. Measures: Face‐to‐face, audio‐recorded, semi‐structured interviews were conducted and transcribed verbatim. Other data sources included field notes of approximately 100 hours of field work, windshield surveys, and a focus group. Data were analyzed using Spradley's guidelines. Results: The significant family health concern was "diabetes runs rampant here" with inter‐related cognitive, emotional, and behavioral responses. These responses were compounded by accumulated emotional trauma from witnessing premature deaths and severe comorbidities associated with diabetes. Contextual factors shaping "diabetes runs rampant here" were identified. Conclusion: Holistic approaches are urgently needed in diabetes prevention and management programs. Implications for public health nurses are discussed and recommendations are provided for future research.